2021
DOI: 10.1021/acssuschemeng.1c03811
|View full text |Cite
|
Sign up to set email alerts
|

In Competition for Water: Hydrated Choline Chloride:Urea vs Choline Acetate:Urea Deep Eutectic Solvents

Abstract: Unlike the archetypal deep eutectic solvent (DES) choline chloride:urea (ChCl:U), fundamental knowledge of the intermolecular network in choline acetate (ChOAc) DESs and how they change upon dilution is still missing. Here we jointly use UV resonance Raman (UVRR) and NMR spectroscopy to comparatively explore how the strength and distribution of hydrogen bonding and the solvation of the components are modified in ChOAc:U and ChCl:U with increasing hydration. Overall, Raman and NMR data indicate that ChOAc:U is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 73 publications
3
22
0
Order By: Relevance
“…This behavior was predicted from MD simulations and ascribed to a more heterogeneous environment of the NH 2 groups and stronger hydrogen bonds involving the water molecules [11]. Pietro et al [21], also relate the red shift of the NH 2 rocking band observed in Raman spectra with new hydrogen bond interactions of urea with water. In the second region (2,700-3,800 cm −1 , Figure 6B), there are two main broad features, assigned to the CH and NH + OH stretching modes, centered at ca.…”
Section: Effect Of Water In Chcl:urea Desmentioning
confidence: 76%
See 1 more Smart Citation
“…This behavior was predicted from MD simulations and ascribed to a more heterogeneous environment of the NH 2 groups and stronger hydrogen bonds involving the water molecules [11]. Pietro et al [21], also relate the red shift of the NH 2 rocking band observed in Raman spectra with new hydrogen bond interactions of urea with water. In the second region (2,700-3,800 cm −1 , Figure 6B), there are two main broad features, assigned to the CH and NH + OH stretching modes, centered at ca.…”
Section: Effect Of Water In Chcl:urea Desmentioning
confidence: 76%
“…A matter that emerges from a large number of experimental reports is the effect of water on the properties of DES. It has become evident that the effect of water on the physicochemical properties and on the structural features of DES has important practical implications [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Water addition promotes structural changes on DES at the microscopic level and these changes are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Based on our previous findings that DESs can behave as non-innocent reaction media in catalyzing the cyclization/aromatization of nitrogen heterocycles, [15,16] we next turned our attention towards a different DES, namely choline acetate (ChOAc)/urea (1 : 2 mol mol À 1 ), whose components are both basic, and in which protons are more easily exchanged. [23] To our delight, using up to 2 equiv. of base, not only the range of yields increased up to 77-98 % with 7 educts (3 a-e, 3 g,h) now isolated in 98 % yield, but the reaction time, in some cases, also shortened up to 2-4 h (3 a-c, 3 g) (Scheme 2).…”
Section: Resultsmentioning
confidence: 97%
“…This is based on a cycloaddition‐elimination cascade reaction between aryl azides and enol ethers to access either 1,4‐ or 1,5‐disubstituted triazoles [22] . Based on our previous findings that DESs can behave as non‐innocent reaction media in catalyzing the cyclization/aromatization of nitrogen heterocycles, [15,16] we next turned our attention towards a different DES, namely choline acetate (ChOAc)/urea (1 : 2 mol mol −1 ), whose components are both basic, and in which protons are more easily exchanged [23] . To our delight, using up to 2 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…Further features in the fingerprint region cannot be assigned and could also be the result of subtle modifications in the spectra caused by varying water concentrations in NADES. It has been reported in the literature that molecular interactions can be affected by water concentrations in NADES, associated with a weakening of the hydrogen bonding between HBD-HBA, H 2 O-HBD and H 2 O-HBA, which can be observed by Raman spectroscopy [ 85 , 86 , 87 ]. However, the OH scissoring bending band from water at ~1633 cm −1 is weak compared to the other bands and, due to the overlap with the L-Proline band at 1624 cm −1 , its contribution to the PLSR model is not significant.…”
Section: Resultsmentioning
confidence: 99%